2010
DOI: 10.1016/j.neuropsychologia.2010.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Altered connectivity between prefrontal and sensorimotor cortex in conversion paralysis

Abstract: a b s t r a c tConversion paralysis (CP) is a frequent and impairing psychiatric disorder, affecting voluntary motor function. Yet, we have previously shown that the motor system of CP patients with a unilateral conversion paresis is recruited to a similar degree during imagined movements of the affected and unaffected limb. In contrast, imagery of movements with the affected limb results in larger prefrontal activation. It remains unclear how this hand-specific increased prefrontal activity relates to the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 67 publications
7
43
1
1
Order By: Relevance
“…Cojan et al 41 in their comparison of one patient with functional paralysis and 30 healthy volunteers using the go/no-go task also showed greater FC between the VMPFC, precuneus, and posterior cingulate cortex with right M1, suggesting a role for selfrelated representations or emotions in influencing voluntary motor activity (Figure 2). These findings are contrasted with that of de Lange et al, 22 who did not show any connectivity between VMPFC and sensorimotor regions in a comparison of the affected versus unaffected sides using self-related motor imagery. This enhancement in attention to self or self-monitoring has been proposed to play a role in increasing the precision of priors, expectations and beliefs, as further discussed below.…”
Section: Self-monitoring or Attention To Selfcontrasting
confidence: 99%
See 2 more Smart Citations
“…Cojan et al 41 in their comparison of one patient with functional paralysis and 30 healthy volunteers using the go/no-go task also showed greater FC between the VMPFC, precuneus, and posterior cingulate cortex with right M1, suggesting a role for selfrelated representations or emotions in influencing voluntary motor activity (Figure 2). These findings are contrasted with that of de Lange et al, 22 who did not show any connectivity between VMPFC and sensorimotor regions in a comparison of the affected versus unaffected sides using self-related motor imagery. This enhancement in attention to self or self-monitoring has been proposed to play a role in increasing the precision of priors, expectations and beliefs, as further discussed below.…”
Section: Self-monitoring or Attention To Selfcontrasting
confidence: 99%
“…Both patients with essential tremor and healthy controls activated the supplementary motor area (SMA) and deactivated the visual cortex, whereas individuals with functional tremor activated the cerebellum. In the same study by de Lange et al, 22 the authors showed greater functional connectivity (FC) of the affected hand, compared with the unaffected hand, between the left DLPFC and sensorimotor regions, including the SMA. Focusing on the motor intention phase of movement, Voon et al 23 showed decreased activity in the SMA and increased activity in limbic regions (amygdala, anterior insula) among patients with functional motor symptoms (N=11) compared with healthy volunteers (Figure 2).…”
Section: Motormentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have found alterations in other regions such as the frontal cortex and the lower OFC ( Vuilleumier, 2005). Studies based on various paradigms suggest that there may be a disconnection between the dorsolateral prefrontal cortex (dlPFC) and motor areas (Marshall et al, 1997;Spence et al, 2000;De Lange et al, 2010). The OFC and ACC have been identified as responsible for the inhibitory effects of the dlPFC over the motor cortex (Marshall et al, 1997;Halligan et al, 2000;Amoruso, 2010).…”
Section: Motor Loss: Paralysis and Paresismentioning
confidence: 99%
“…Az eredmények azonban fenntartásokkal kezelen-dők, mivel szinte az összes vizsgálati személyt depresszióval is diagnosztizálták; hasonló strukturális eltéréseket pedig depresszióban is kimutattak [51].…”
Section: Organicitásunclassified